Effect of Positive Airway Pressure During Preoxygenation on Safe Apnea Period: a comparison of the supine and 25° head up position - Dhakal, Y.; Bhattarai, B.; Khatiwada, S.; Subedi, A. (Kathmandu University Medical Journal, 2020)
Background Preoxygenation is performed before induction of anaesthesia which increases oxygen reserve and provides delayed onset of hypoxia during period of apnea. Several techniques such as positive airway pressure and head-up tilt during preoxygenation have shown to prolong safe apnea period compared to conventional technique. However, uniform recommendations have not yet been made.Objective To find out the effect of combination of 5 cmH2O continuous positive airway pressure (CPAP) and 25° head up position during preoxygenation on safe apnea period.Method In this comparative study 60 non-obese adult patients were divided into three equal groups; Group C receiving preoxygenation in conventional technique, Group S receiving preoxygenation with 5 cmH2O continuous positive airway pressure in supine position and Group H receiving preoxygenation in 25° head-up position with 5 cmH2O continuous positive airway pressure . After 3 min of preoxygenation, intubation was performed after induction of anaesthesia with propofol, fentanyl and succinylcholine. After confirming the tracheal intubation by direct visualization, all patients were administered vecuronium to maintain neuromuscular blockade. Post-intubation, patients in all groups were left in same position with the tracheal tube exposed to atmosphere and without being ventilated till the SpO2 dropped to 92%. The primary outcome compared between the groups was the safe apnea period (time from loss of consciousness to fall of SpO2 to 92%).Result The duration of safe apnea period was longer (p < 0.05) in Group H patients (405.9 ± 106.69 s) as compared to the Group C (296.9 ± 99.01s) and Group S (319.65 ± 71.54s). Although the duration of safe apnea period was longer in the Group S as compared to Group C the difference was not statistically significant.Conclusion Preoxygenation in 25° head-up position with 5 cmH2O continuous positive airway pressure significantly prolongs safe apnea period in non-obese adults compared to supine position, with or without 5 cmH2O continuous positive airway pressure.